UNLOCKING THE ANTI-HYPERURICEMIA POTENTIAL OF Arcangelisia flava STEM: AN IN VIVO STUDY IN HYPERURICEMIC RATS - Fatmawati; Attallah Perdana Akbar; Medina Athiah; Eka Handayani Okhtarina (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Hyperuricemia is a condition of increased uric acid levels in the blood that can trigger gout and other metabolic disorders. Conventional therapies such as allopurinol are effective, but have side effects, so safer natural alternatives are needed. Arcangelisia flava, a traditional medicinal plant, is known to contain bioactive compounds with anti-inflammatory and antioxidant potential. This study aims to evaluate the anti-hyperuricemic effect of ethanol extract of A. flava stems in vivo in potassium oxonate-induced rats. Rats were divided into control groups, hyperuricemia models, and treatments with extract doses of 100, 200, and 400 mg/kg BW. Uric acid levels were measured enzymatically before and after treatment. The results showed that A. flava extract significantly reduced uric acid levels (p=0.000), especially at a dose of 400 mg/kg BW which reduced uric acid levels by 74.17%. These findings support the potential of A. flava as a natural anti-hyperuricemic agent.